Development of a Production Process for Biomass-Based Activated Carbon via Hydrothermal Carbonization Method - Katı, Nida; Ucar, Ferhat (My University, 2024)
This study presents a process development including detailed characterization of hydrochars and activated carbons produced by hydrothermal carbonization and chemical activation methods using apricot kernel shells (AKS). Initially, the AKS were processed by grinding, followed by subjecting them to hydrothermal carbonization at 240ºC for 24, 36, and 48 hours, resulting in three distinct hydrochars. Subsequently, these hydrochars were mixed with KOH for 3 hours and subjected to a carbonization process at 700°C for 1 hour to obtain activated carbons. Various characterization methods such as Brunauer-Emmett-Teller (BET) surface area analysis, Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS), X-Ray Diffraction (XRD) analysis, and Fourier-Transform Infrared spectroscopy (FTIR) measurements were employed to determine the properties of the activated carbons. The results obtained indicate that the duration of the hydrothermal reaction increases the carbon content and leads to the formation of porous structures. Particularly, the chemical activation process was found to be effective in pore formation, as evident in SEM images. In conclusion, this study provides a detailed description of the characteristic properties of hydrochars, and activated carbons derived from AKS.
Keywords: Activated carbon; Hydrothermal carbonization; Apricot kernel shell